2017
DOI: 10.1088/1757-899x/171/1/012131
|View full text |Cite
|
Sign up to set email alerts
|

Final design, fluid dynamic and structural mechanical analysis of a liquid hydrogen Moderator for the European Spallation Source

Abstract: Abstract. The European Spallation Source (ESS) is currently in the construction phase and should have first beam on Target in 2019. ESS, located in Sweden, will be the most powerful spallation neutron source worldwide, with the goal to produce neutrons for research. As an inkind partner the Forschungszentrum Juelich will among others, design and manufacture the four liquid hydrogen Moderators, which are located above and below the Target. Those vessels are confining the cold hydrogen used to reduce the energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 1 publication
0
18
0
Order By: Relevance
“…Page 80: Redundant reference in section 3.3.3. The [137,141] in the first paragraph should be corrected to [137], removing [137,141].…”
Section: Institutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Page 80: Redundant reference in section 3.3.3. The [137,141] in the first paragraph should be corrected to [137], removing [137,141].…”
Section: Institutionmentioning
confidence: 99%
“…Figure 83 shows the fluid dynamic behaviour of the cold collimator system, over five beam pulses [137].…”
Section: Institutionmentioning
confidence: 99%
“…( 1). Lehmann et al [8] reported that a transient heat flux for loss of insulation vacuum for LHe cryostat and LHe containers with MLI was 6 2 . In this analysis, the heat flux of 6 kW/m 2 is always applied to the process line, regardless of the vacuum pressure.…”
Section: 𝑚̇= 𝐶mentioning
confidence: 99%
“…In the beginning, the ESS will install two hydrogen moderators above the target wheel and the current plan is to replace them with four (two above and two below, respectively) in the future. Two flat butterfly shaped hydrogen moderator vessels have been designed and optimized to achieve a maximum neutron brightness under the condition of parahydrogen fraction higher than 99.5% [2]. A cryogenic moderator system (CMS) has been designed to continuously supply subcooled liquid hydrogen with a temperature of 17 K and a parahydrogen fraction of more than 99.5% to the moderators and to maintain an average temperature rise at the moderators within 3 K [3].…”
Section: Introductionmentioning
confidence: 99%
“…The cold moderators form a flat butterfly shape, which are optimized to achieve a high cold neutron brightness. The neutronic performance of the cold moderators degrades rapidly with the decreasing parahydrogen fraction below 99.5% [4]. The neutron collisions in the cold moderators increases the orthohydrogen fraction [5] if it is not compensated by the ortho-to parahydrogen conversion driven by the catalyst system.…”
Section: Introductionmentioning
confidence: 99%